Clinical evaluation of a trabecular microbypass stent with phacoemulsification in patients with open-angle glaucoma and cataract - Ferguson, Tanner J (Clin Ophthalmol, 2016)
PURPOSE: To evaluate the safety and efficacy of the iStent trabecular microbypass stent in combination with cataract surgery in patients with open-angle glaucoma (OAG). METHODS: Retrospective, consecutive case series from October 2012 to December 2015 with no exclusion criteria. The series comprised of 350 eyes with OAG and cataract. Data were collected both preoperatively and postoperatively at day 1 week 1, months 1, 3, 6, 12, 18, and 24. Data included intraocular pressure (IOP), number of glaucoma medications, visual acuity, the incidence of postoperative IOP pressure spikes of greater than ≥15 mmHg at any time point, and need for additional surgery. RESULTS: The mean preoperative IOP was 19.13±6.34 mmHg. At 2 years postoperation, mean IOP was 15.17±3.53 mmHg (P<0.0001). The mean number of glaucoma medications was 1.19±1.00 preoperatively and 0.61±0.96 (P<0.0001) at 2 years postoperation. At 1 day postoperatively, 31 eyes (12.4%) experienced an IOP increase of 15 mmHg above their baseline IOP that responded to topical therapy. Two patients required additional tube shunt surgery. CONCLUSION: The insertion of the iStent trabecular microbypass stent in combination with cataract surgery effectively lowers IOP in OAG patients. The magnitude of IOP reduction was more significant in patients with higher preoperative pressure. Medication use was also significantly reduced postoperatively. The safety profile appears favorable with a low rate of IOP spikes and only two eyes (<1%) requiring additional surgery.